2021
DOI: 10.1253/circj.cj-20-1116
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Recovery From Takotsubo Syndrome Is a Major Determinant of Cardiovascular Mortality

Abstract: Background: Although there is an apparent rapid and spontaneous recovery of left ventricular ejection fraction (LVEF) in patients with Takotsubo syndrome (TTS), recent studies have demonstrated a long-lasting functional impairment in those patients. The present study sought to evaluate the predictors of incomplete recovery following TTS and its impact on cardiovascular mortality. Methods and Results:Patients with TTS between 2008 and 2018 were retrospectively enrolled at 3 different institutions. After exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Although an improvement of LVEF after CS can be observed in a considerable number of patients following coronary revascularization, recovery from severe inflammation, volume optimization, and introduction of HF drugs, adverse clinical events may occur as a consequence of adverse cardiac remodeling, residual ischemia, incomplete LVEF recovery, or progression of the baseline diseases, 6 , 24 , 25 , 26 which all can be targeted by beta blockers, RASI, and MRA, which compose the triple GDMT. 6 , 24 , 27 Although there has been no randomized clinical trial that investigated the effects of HF drugs at the recovery phase of patients with CS, the recent STRONG‐HF (Safety, Tolerability and Efficacy of Rapid Optimization, Helped by NT‐proBNP Testing, of Heart Failure Therapies) trial demonstrated that rapid titration of GDMT using beta blockers, RASI, and MRA reduced the risk of 180‐day all‐cause death or HF hospitalization in patients with acute HF without shock.…”
Section: Discussionmentioning
confidence: 99%
“…Although an improvement of LVEF after CS can be observed in a considerable number of patients following coronary revascularization, recovery from severe inflammation, volume optimization, and introduction of HF drugs, adverse clinical events may occur as a consequence of adverse cardiac remodeling, residual ischemia, incomplete LVEF recovery, or progression of the baseline diseases, 6 , 24 , 25 , 26 which all can be targeted by beta blockers, RASI, and MRA, which compose the triple GDMT. 6 , 24 , 27 Although there has been no randomized clinical trial that investigated the effects of HF drugs at the recovery phase of patients with CS, the recent STRONG‐HF (Safety, Tolerability and Efficacy of Rapid Optimization, Helped by NT‐proBNP Testing, of Heart Failure Therapies) trial demonstrated that rapid titration of GDMT using beta blockers, RASI, and MRA reduced the risk of 180‐day all‐cause death or HF hospitalization in patients with acute HF without shock.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cohort studied, the average LVEF improved from 41.1% to 59.9% within 2 months [ 11 ]. However, recent studies have reported incomplete LVEF recovery from TTS, characterized by residual systemic inflammation and increased cardiac mortality at follow-up [ 18 ]. The recovery time for TTS patients is also clinically important.…”
Section: Discussionmentioning
confidence: 99%
“…The increased level of proinflammatory cytokines persists for several months after the onset of TTS symptoms, which suggests a low-grade chronic inflammatory state [18]. Moreover, residual high systemic inflammation, defined as increased levels of C-reactive protein at discharge, is a predictor of incomplete recovery after the acute phase of TTS and is an independent factor of cardiovascular events [20,28]. Recently, it has been shown that patients with TTS have higher ultra-small iron oxide superparamagnetic particle (USPIO) retention in the LV during the acute phase, regardless of the ballooning or non-ballooning segment, when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%